PENGEMBANGAN E-MODUL DENGAN PENDEKATAN RME UNTUK MENDUKUNG KEMAMPUAN LITERASI MATEMATIS SISWA SMP/MTs - Vina Rohmatika; Khaerunnisa, Etika; Rafianti, Isna (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The purpose of this research is to determine the levels of validity, practicality, and effectiveness of an e-module using the Realistic Mathematics Education (RME) approach to support the mathematical literacy skills of junior high school (SMP/MTs) students on the topic of systems of linear equations with two variables. This study is a type of development research (research and development) employing the ADDIE model. The validation results indicate that the content experts achieved a percentage score of 92% in the